Reassessing the two-stage theory of social learning development: a discussion - Shang, Yaming; Xia, Yaoru; Yin, Yating; Dong, Da (Frontiers in Psychology, 2025)
This article reevaluates the two-stage development theory of social learning by examining the distinct roles of pedagogical and selective learning. Pedagogical learning involves infants’ sensitivity to adults’ communicative intentions, while selective learning highlights how infants prioritize information from reliable sources. Over time, the influence of pedagogical learning diminishes, whereas selective learning continues to play a central role as children grow. We argue for the distinctiveness and plurality of human social learning and emphasize the foundational role of multiple social interactions in cognitive development. Special attention is given to the transition from reliance on pedagogical cues to selective learning, underscoring the critical role of educators in facilitating this shift. We conclude by highlighting the increasing sophistication of cognitive and social selection processes in observation, imitation, and learning, alongside the implications for educational practices. Future research should investigate differences between social and other forms of learning, the mechanisms underlying the diminishing effects of pedagogical cues with age, the cultural variability in social learning trajectories, and the impact of educational technology on the development of social learning.